Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1073/pnas.94.7.3016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel pathway important for proliferation and differentiation of primary erythroid progenitors

Abstract: Homodimerization of the erythropoietin (EPO) receptor (EPO-R) in response to EPO binding transiently activates the receptor-associated protein tyrosine kinase JAK2. Tyrosine phosphorylation of the EPO-R creates ''docking sites'' for SH2 domain(s) in signaling molecules such as the protein tyrosine phosphatases SH-PTP1 and SH-PTP2, phosphoinositide 3-kinase (PI3 kinase), and STAT5. However, little is known about the specific intracellular signals essential for proliferation and differentiation of erythroid prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(154 citation statements)
references
References 33 publications
(40 reference statements)
5
146
2
1
Order By: Relevance
“…These discrepancies may be due to di erences in cell lines and highlight the problems of an in vitro, cell line-based analysis of STAT function, where cells may be lacking other critical components of the di erentiation process. Indeed, the expression of mutant EpoRs into fetal liver cells derived from EpoR (7/7) mice has revealed that the receptor that best reconstitutes erythropoiesis does not correlate with the ability to activate STAT5 but rather the phosphatidylinositol lipid kinase, PI3K (Klingmuller et al, 1997).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…These discrepancies may be due to di erences in cell lines and highlight the problems of an in vitro, cell line-based analysis of STAT function, where cells may be lacking other critical components of the di erentiation process. Indeed, the expression of mutant EpoRs into fetal liver cells derived from EpoR (7/7) mice has revealed that the receptor that best reconstitutes erythropoiesis does not correlate with the ability to activate STAT5 but rather the phosphatidylinositol lipid kinase, PI3K (Klingmuller et al, 1997).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…48 Mutant EpoRs capable of activating only a subset of these signal transduction proteins, for instance only STAT5 or only PI-3 kinase, are capable of supporting normal in vitro differentiation of primary erythroid progenitors from EpoR −/− mice. [49][50][51][52][53] Thus, many of the signaling pathways activated by the EpoR appear redundant. None of these signal transduction proteins are unique to the EpoR and most are activated by a large number of other cytokine receptors as well as BCR-ABL and other types of growth factor receptors.…”
Section: Domains In Bcr-abl Important For Transformationmentioning
confidence: 99%
“…Upon hormone binding the epo receptor dimerizes, Janus kinase 2 (JAK2) is activated and tyrosine residues in the cytoplasmic domain of the receptor phosphorylated (Matthews et al, 1996;Watowich et al, 1992;Witthuhn et al, 1993). These phosphorylated tyrosines act as docking sites for signaling proteins including Signal Transducer and Activator of Transcription 5 (STAT 5), the p85 subunit of phosphatidylinositol 3-kinase (PI3-kinase) and phosphatases SHP-1 and SHP-2 (Damen et al, 1995a,b;Gobert et al, 1996;Klingmuller et al, 1995Klingmuller et al, , 1996Klingmuller et al, , 1997Penta and Sawyer, 1995;Quelle et al, 1996;Sharlow et al, 1997;Tauchi et al, 1995Tauchi et al, , 1996Yi et al, 1995). Although Shc and Grb2 bind to the epo receptor and stimulate the Ras/Raf/MAP-kinase pathway (Barber et al, 1997;Bittorf et al, 1994;Carroll et al, 1991;Cutler et al, 1993;Gobert et al, 1995;He et al, 1995;Miura et al, 1994b;Tilbrook et al, 1996a;Torti et al, 1992), their precise binding locations on the receptor have not been identi®ed.…”
Section: Introductionmentioning
confidence: 99%